METODE DEKOMPOSISI MULTIPLIKATIF RATA-RATA BERGERAK UNTUK PERAMALAN TINGKAT PRODUKSI PADI LADANG SULAWESI TENGAH - Kadoena, Faldi Christiawan; Rais, Rais; Handayani, Lilies (Univ. Tadulako, 2019)
Field rice is a rice plants that is planted in a sedentary or shifting location. This study aims to forecast field rice production using the Multiplicative Decomposition method of moving average, and to determine the size of forecasting accuracy using Tracking signal, data used is the data from Central Sulawesi Province Field rice production in 2008-2016 obtained from the Agriculture Service of Central Sulawesi Province The research procedure is begun by analyzing the components of decomposition, namely the components of trend (T), seasonal (S), cyclic (C) and random components (I) then multiplies the value of these components. Forecasting results using the decomposition method helping by the Minitab 18 application in 2017 show that the pattern of the data contains a declining trend with the equation Yt = 1895.60 - 7.97 × t, and has a strong seasonal pattern with the expected pattern of data that increases or decreases in certain months such as March, April, August and December. The forecasting results obtained are at the control limit of Tracking signal which is between -4 to +4 that means the forecasting of rice production in the province of Central Sulawesi in 2017 using the moving average Multiplicative Decomposition method is valid